The effect of failure on performance over time: The case of cardiac surgery operations - Avgerinos, Emmanouil; Fragkos, Ioannis; Gokpinar, Bilal (Wiley, 2019)
Failure is a common occurrence in many operational contexts involving knowledge work. Concentrating on highly critical cardiac surgery operations, we investigate how failure affects subsequent performance over time. In addressing our research questions, we draw on the sensemaking perspective and incorporate behavioral aspects of failure that are often overlooked. We develop three hypotheses on the effects of failure (i.e., in-hospital mortality of a patient) and test them with a unique data set of 4,306 cardiac surgery operations from a large European hospital, spanning five years. Our findings show that while failure promotes learning over time and improves task execution quality (as measured by patients' reduced length of stay) in the long term, its effect is the opposite in the short term. Our work also unravels how relational dynamics (i.e., familiarity) may reduce the short-term effects of failure. We find evidence that team familiarity mitigates the detrimental effects of recent failures. This implies that certain team assignment strategies after failure (e.g., putting individuals into familiar teams) may be preferable than others. We explore and illustrate this by conducting a policy simulation based on our data. This article provides new insights into how operations managers can support their employees in moving forward after failure.
Keywords: Healthcare operations; Failure; Sensemaking; Quality; Team familiarity; 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 3 - Salud y bienestar